NbC transformation during aging in HP40-Nb heat resistant alloy - Sosa Lissarrague, Matías Humberto (2022)
In this work, the evolution of MC-type Nb-rich primary carbides in a 35Ni-25Cr-Nb-type refractory alloy, commonly known as HP40-Nb, and its transformation into Ni-Nb silicide known as G-phase (Ni16Nb6Si7), has been studied. For this purpose, the exper-imental technique of scanning electron microscopy was used together with X-ray microanalysis to detect changes in the chemical composition of niobium carbide over time and at a given aging temperature. The microstructure of the studied alloy, in its as-cast condition, consists of an austenitic matrix strengthened by a network of primary eutectic-like carbides rich in chromium and niobi-um of the M23C6 and MC types, respectively. During aging of the alloy at high temperatures, microstructural changes take place such as the secondary precipitation of M23C6 type carbides and the transformation of the primary Nb-rich carbide towards the Ni-Nb-rich silicide. It has been found that the transformation begins at the interface of the niobium carbides with the matrix, progress-ing towards their interior with the development of aging.